Hahira Gold Leaf, January 27, 1972 - Hahira Historical Society (Valdosta State University Archives and Special Collections, 1972)
Digital surrogate of the Hahira Gold Leaf newspaper for January 27, 1972 from the Hahira Historical Society Collection at Valdosta State University Archives and Special Collections.
1 electronic record (PDF), and 8 page scans (JP2). 1.35 GB (1,451,418,861 bytes)
Keywords: Hahira (Ga.); Lowndes County (Ga.); Newspapers; Periodicals; Georgia -- Hahira -- Newspapers; Local history